The Effect of Promotion, Product Review, and Security on Purchasing Decision - Jizenji Tyas Wirastomo; Langgeng Sri Handayani (Jurnal Syntax Transformation, 2022)
This research uses qualitative methods through field surveys of a sample of Tokopedia Online Store site is one of the Indonesian marketplaces for buying and selling online. and the most visited in 2021. Promotions, Product Reviews, Security of the Tokopedia Application can affect purchase intentions using the Tokopedia Application. The purpose of this study was to determine the effect of promotions, product reviews, and application security on purchasing decisions using the Tokopedia application at the Bekasi Civil Society Communication Forum. The population of 1771 members, 100 samples, and research samples were obtained using the Slovin formula with a standard error of 10%. There were 95 respondents who appeared. The results of this study indicate that there is a positive effect of promotional variations (X1) on purchasing decisions (Y) from these variables. Product evaluation variable (X2) has a positive effect on purchasing decisions (Y). There is a positive effect of the security variable (X3) on purchasing decisions (Y). The Adjusted R-squared value of 0.720 indicates that 70.2% of the variation in purchasing decisions can be explained by the three independent variables in the regression equation.